Disfagia dalam Perspektif Klinis Kontemporer - Raymond R. Tjandrawinata (MEDICINUS, 2026)
Dysphagia is a clinical symptom with diverse etiologies that is often narrowly interpreted as a neurological disorder or mechanical obstruction, however, recent literature indicates that it may present as a dominant symptom in chronictonsillopharyngitis with acute exacerbation. This narrative perspective review discusses the variability of dysphagia manifestations, underlying pathophysiological mechanisms, and the implications for management in inflammatorytonsillopharyngitis compared to dysphagia due to stroke, neurological, and neoplastic conditions, emphasizing that inflammatory dysphagia related to tonsillopharyngitis is potentially reversible and gives favourable response to cultureguidedantibiotics, short-term corticosteroids, as well as dietary modification. Early recognition of these clinical variations is essential to improve diagnostic accuracy and patients’ quality of life.dysphagia, chronic tonsillopharyngitis, acute exacerbation, oropharynx inflammation, clinical management